What Determines the Duration of Stay of Immigrants in Germany? Evidence from a Longitudinal Duration Analysis - Sebastian Gundel; Heiko Peters (Deutsches Institut für Wirtschaftsforschung (DIW), 2008)
We analyze the return-migration of German immigrants using the latest data of the German Socio- Economic Panel from 1984 to 2006. We conduct a Cox proportional hazard model with years of residence in Germany as waiting time. The analysis reveals that return migration is heavily influenced by country of origin. Individuals from countries with free labor movement agreements with Germany show a considerably higher likelihood of leaving the country relative to the others. The main finding is, with respect to the self-selection process we discovered that highly skilled are more likely to return than the less skilled. In addition, the results give plenty of information regarding the design of German immigration policy.
Keywords: C41; F22; J10; J61; 330; Remigration; Cox proportional hazard model; Germany